2019
DOI: 10.1111/jocn.14734
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ experiences of donation to their child before kidney transplantation: A qualitative study

Abstract: Aim and objectives To explore parents’ experiences of donation to their child before kidney transplantation. Background Transplantation is the treatment of choice for paediatric patients with end‐stage renal disease. Living donor kidney transplantation has shown a higher long‐term transplant survival compared to deceased donor transplantation and entails a more controllable process, with shorter waiting time. Besides complex care and treatment of their child, parents must reflect on the prospects of being a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…One contribution of our study was to find differences between women when delving more deeply into this aspect. Moreover, as other studies [38,60], participants with biological kinship bonds said that they saw their donation as a 'natural thing', as the natural consequence of family bonds, as a matter of course within the family. We understand this normality as a social construction that is framed in a certain context [61].…”
Section: Discussion/conclusionmentioning
confidence: 91%
“…One contribution of our study was to find differences between women when delving more deeply into this aspect. Moreover, as other studies [38,60], participants with biological kinship bonds said that they saw their donation as a 'natural thing', as the natural consequence of family bonds, as a matter of course within the family. We understand this normality as a social construction that is framed in a certain context [61].…”
Section: Discussion/conclusionmentioning
confidence: 91%
“…However, if they did not grasp the family's difficult and complex situation, this could lead to frustration and disappointment. One study found that talking to friends and family, for example about the need for a kidney donor, could be followed by feelings of vulnerability and disappointment if those who were asked declined (Agerskov et al, ). Geense et al () found that parents turned to their family and friends for a listening ear, understanding and sympathy and to share their emotions and feelings.…”
Section: Critical Interpretation and Discussionmentioning
confidence: 99%
“…Managing an everyday life with a child on haemodialysis has a long‐term impact on a variety of psychosocial areas, including the parents’ relationship, social lives and mental well‐being (Tong et al, ). Further, thoughts about the child's need for a kidney transplantation cause reflections of finding a suitable donor and fear of onset of dialysis treatment and the need of being referred to the transplant waiting list (Agerskov, Thiesson, Specht, & Pedersen, ). In addition, parents experience difficulties in balancing the needs of their child with their other responsibilities, such as work, social life and other family members’ needs (Law, Fisher, Eccleston, & Palermo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Parents may worry that a suitable organ will not be found in time due to the long waiting times children endure when compared to adults, in the UK alone. Despite every stakeholder's effort to find a viable organ(s) for transplant, it can take a long time as waiting lists continue to grow, and if waiting times persist, there is the possibility that their child could die waiting (Agerskov et al, 2018).…”
mentioning
confidence: 99%
“…The potential risks of transplantation are embedded in parents’ minds thereafter, especially in those who are better educated about their child's illness. More knowledge about their child's illness increases fears of uncertainty relating to transplant complications, the child's prognosis and where they fit into the family unit, thus causing parental stress that leads to poor clinical outcomes as poorer family function links to a decline in medication adherence (Agerskov et al, 2018; Anthony et al, 2014; Walker et al, 2019).…”
mentioning
confidence: 99%